Aproveitamento de coprodutos do biodiesel: torta de girassol e glicerina bruta em rações para poedeiras comerciais - Costa, Monik Kelly de Oliveira (2019)
The objective of this study was to evaluate the effects of the inclusion of sunflower cake and crude glycerin in the feeding of lightweigh (white) and semi-heavy (brown) layers in egg production and quality, the amount of phenolic compounds, the antioxidant capacity (DPPH and ABTS) in dehydrated eggs, fresh egg yolk lipid oxidation (TBARS) in fresh and stored eggs, as well as lipid oxidation in serum in lightweigh laying hen. For this, two experiments were performed, in which 320 laying hens in each trial (laying hens light on the first and laying hens semi-heavy on the second) were distributed in a completely randomized design, in a 4x2 factorial scheme with four inclusion levels of sunflower cake (0, 7, 14 and 21% for light laying hens and 0, 9, 18, 27% for semi-heavy laying hens) and two inclusion levels of crude glycerin (0 and 7%). For the light and semi-heavy laying hens, the highest inclusion level (21 and 27%, respectively) of the sunflower cake used in this study reduced egg mass and worsened feed conversion. Evaluating the egg quality of laying hens, inclusion of sunflower cake from the 7% level reduced the color of the egg yolk. There was interaction for the specific density of laying hens eggs, where reduction in specific density occurred when sunflower cake was included in glycerin feed. The lipid oxidation in the liver of lightweight laying hens increased with the addition of sunflower cake from the 14% level and with 7% crude glycerin in the rations. Evaluating the egg quality of semi-heavy hens, there was a reduction in the specific density of the eggs and the color of the yolk from the level of 18% in the rations. The addition of 7% crude glycerin in the feed impaired the eggshell quality. There was significant interaction for the color variable of the yolk, in which the inclusion of sunflower cake from the 18% level in glycerin diets reduced the color intensity of the yolk. The analysis of the economic viability of the rations showed that it is possible to include the tested ingredients in light and semi-weight egg-laying rations without presenting losses to the producer. The antioxidant capacity by the DPPH method increased when 21% for light birds or 18 and 27% for sunflower cake for semi-heavy birds was included. However, by the ABTS method, the antioxidant capacity increased with the inclusion of 14 and 21% of sunflower cake for light birds, but for semi-heavy birds, only the 27% level had an effect. The inclusion of 7% of crude glycerin in the diet of light and semi-heavy layers increased the lipid oxidation of fresh and stored egg yolk. Lipid oxidation in the fresh egg yolk reduced with the inclusion of 7% sunflower cake in the light weight laying hen ration and at all levels of inclusion of this ingredient in the semi-heavy hens. On the eggs of light laying hens fed with ration containing 7% crude glycerin stored for 28 days, the inclusion of sunflower cake increased lipid oxidation reaching the maximum value at the estimated level of 10.71%, reducing oxidation at higher levels to this.